PROSES ORGANIC ELECTROCOATING YANG RAMAH LINGKUNGAN - Sri Mulyaningsih (Pusbindiklat - LIPI, 2010)
Organic electrocoating process is the plating process using organic material to be plate on the conductor materials. The process is almost the same with other electroplating process, but they have several benefits such asno hazardous content, the plating sequence more shorter than electroplating process, and is possible to depositeng clear or tinted polyurethane plating. The organic electrocoating steps consist of surface treatment which is immersing the sample to the alkaline soak cleaner solution than acid mild dipping, continue to deionised rinse, organicelectrocoating, deionised rinse, post dye, and curing. The result of the experiment shows that the optimal Organic electrocoating process is held at voltage 35–40 V to give the best surface layer.